Regional secondary school consolidation: theorizing an innovative model. Issue 3 (4th May 2021) - Eacott, Scott
ABSTRACT: This paper engages with an innovative approach to school consolidation in regional New South Wales, Australia. Adopting a 'one school, two sites' model, it is argued that this innovative approach to school consolidation requires new theoretical resources to understand 'the school'. Theoretically informed by Eacott's relational approach and drawing on publicly available data (e.g. MySchool) and focus groups with school leaders, this paper argues that: (i) complicity with the idea and materiality of 'the school' makes it difficult to thinking differently about schooling; (ii) the image of the school is at once constitutive of, and emergent from, community identity; and (iii) to articulate an alternative requires a shift away from an entity-based (substantialist) perspective. Working with the three key concepts of the relational approach – organizing activity, auctor, and spatio-temporal conditions – this paper proposes an alternate way of thinking about school consolidation and the intellectual resources to do so.